2018
DOI: 10.1186/s12888-018-1754-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of child maltreatment on non-suicidal self-injury: data from a representative sample of the general population

Abstract: BackgroundChild maltreatment is an identified risk factor for Non-Suicidal Self-Injury (NSSI). The aim of the current study was to investigate effects of different types of maltreatment, and mediating effects of depression and anxiety on NSSI in the general population.MethodsA representative sample of the German population, comprising N = 2498 participants (mean age = 48.4 years (SD = 18.2), 53.3% female) participated in this study. Child maltreatment was assessed using the Childhood Trauma Questionnaire (CTQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
73
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 35 publications
14
73
0
8
Order By: Relevance
“…A third possibility is that prior studies may be detecting inflammatory consequences of self-harm as opposed to antecedents, as the act of self-harm itself will trigger an immune response and thus inflammation. Much of the evidence for the inflammation-self-harm relationship comes from crosssectional studies in adult populations, which are unable to establish the direction of association (Brundin, Erhardt, Bryleva, Achtyes, & Postolache, 2015). Our study is also novel in that we explored associations with self-harm regardless of suicidal intent, whereas prior research has focused on suicidal behaviour.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A third possibility is that prior studies may be detecting inflammatory consequences of self-harm as opposed to antecedents, as the act of self-harm itself will trigger an immune response and thus inflammation. Much of the evidence for the inflammation-self-harm relationship comes from crosssectional studies in adult populations, which are unable to establish the direction of association (Brundin, Erhardt, Bryleva, Achtyes, & Postolache, 2015). Our study is also novel in that we explored associations with self-harm regardless of suicidal intent, whereas prior research has focused on suicidal behaviour.…”
Section: Discussionmentioning
confidence: 94%
“…Exposure to adverse childhood experiences (ACEs) is a well-established risk factor for self-harm (Bj€ orkenstam, Kosidou, & Bj€ orkenstam, 2016;Brown et al, 2018;Cha et al, 2018;Dube et al, 2001;Hughes et al, 2017;Liu, Scopelliti, Pittman, & Zamora, 2018); however, the psychological and biological processes underlying this relationship are unclear. Inflammation has been postulated as a potential candidate mechanism, as a growing number of studies have found an association between inflammatory markers and both ACEs (Baumeister, Akhtar, Ciufolini, Pariante, & Mondelli, 2016;Coelho, Viola, Walss-Bass, Brietzke, & Grassi-Oliveira, 2014) and self-harm or suicide (Black & Miller, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Self-injury is thought to be a moderately stable behavior [24], but we do not know whether patterns of recurrence change with increasing age, whether recurrence differs by sex, and what sociodemographic factors, aspects of selfinjury (e.g., age of onset, frequency), and associated mental health problems (e.g., depressive symptoms, suicidal ideation) predict recurrence of self-injury between early adolescence and early adulthood. It is well known that childhood adversity predicts adolescent self-injury, and some of these effects could be mediated by depressive and anxiety symptoms [25,26]. However, prospective studies on whether childhood internalizing symptoms increase the risk of recurrence of self-injury over prolonged periods of adolescence and until early adulthood are currently lacking.…”
Section: Age-related Course and Recurrence Of Self-injurymentioning
confidence: 99%
“…The findings add to prior research, which has revealed that various forms of chronic family adversity, including child maltreatment, relational trauma, lack of support, and hostility, increase the risk of self-injury in adolescents and young adults. These effects have been found to be partially mediated by depressive symptoms, anxiety, and low self-esteem (19,23,47). Research has also shown that more sporadic events involving loss and instability in the family increase young people's risk of suicidality (28), which is a well-known correlate of self-injurious behavior (48,49).…”
Section: Contexts Of Stressful Life Eventsmentioning
confidence: 99%